Rapid identification of chemical composition and metabolites of Pingxiao Capsule in vivo using molecular networking and untargeted data‐dependent tandem mass spectrometry. (6th July 2020) - Wang, Dong; Fu, Zhifei; Xing, Yanchao; Tan, Yao; Han, Lifeng; Yu, Haiyang; Wang, Tao
Abstract: Pingxiao capsule (PXC) is a herbal medicine used for adjuvant therapy in breast cancer. However, the constituents and absorbed components of the formula and their related metabolites have not been elucidated to date. PXC is a typical traditional Chinese medicine formula consisting of Strychnos nux‐vomica L., Curcuma wenyujin Y. H., Agrimonia pilosa Ledeb., Toxicodendron vernicifluum, Trogopterus dung, alumen, potassium nitrate (saltpeter) and Citrus aurantium L. In this study, a ultra‐high performance liquid chromatography system equipped with high resolution Q‐Orbitrap mass spectrometry (MS) and comparative Global Natural Product Social molecular networking together with the Compound Discoverer software were used to identify metabolites of PXC in vitro and in vivo. Based on untargeted data‐dependent MS 2 and data‐mining techniques, 89 peaks of alkaloids, flavonoids, organic acid and phenolic compounds were identified in a PXC 70% methanol extract. Furthermore, 15 absorbed prototype compounds and their metabolites were rapidly confirmed in rat blood. Glucuronidation, oxidation, methylation and hydroxylation were the main metabolic pathways. We fully clarified the chemical constituents of PXC and provided a scientific and efficient strategy for rapid discovery and identification of prototypes and their metabolites in rat plasma using high‐resolution MS aided by Global Natural Product Social and Compound Discoverer software.